PROTOCOL: Situational Crime Prevention Measures to Prevent Terrorist Attacks Against Soft Targets and Crowded Places: An Evidence and Gap Map - Zoe Marchment; Caitlin Clemmow; Paul Gill (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell systematic review. The objectives are as follows. The EGM has three main objectives: (1) Identify the strength (in terms of evidence quality) and depth (in terms of volume of evidence) of evidence base on the efficacy of situational crime prevention measures in preventing terrorist attacks against soft targets and crowded places. (2) Identify the heterogeneity in the effects of situational crime prevention measures against terrorist attacks and link this to issues related to context and implementation. (3) Identify the mechanisms through which situational crime prevention measures have an effect on terrorist attacks. To achieve these objectives, an EGM will seek out reliable quantitative evidence on effect and qualitative evidence on mechanisms, moderators, implementation and economics. Resultingly, it will be possible to identify research gaps and evidence imbalances to facilitate research investment, identify gaps and topics for new research, and provide a foundation for systematic reviews by showing where sufficient evidence exists for aggregation. The underpinning programme of work will result in the presentation of rigorous empirical research on this topic to help researchers and decision‐makers understand the available evidence.